Gastric Cancer: the 25-year R-Evolution - de Manzoni, Giovanni; Roviello, Franco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Twenty-five years ago, a monograph on gastric cancer was published by the Italian Society of Surgery: that book is recognized as a milestone in the management of these tumors in Italy. Oncological and surgical knowledge in the field of gastric cancer have changed dramatically over the last 25 years. The aim of this book is to offer an essential update on current diagnostic approaches and optimal treatment strategies. It gives comprehensive information on gastric cancer not neglecting the basic sciences, which can shed light on the carcinogenesis mechanisms involved in this pathology. The principles of tailored and multimodal treatment are examined according to the latest guidelines with the aim of providing a valuable synopsis for clinicians. The book not only reviews what has changed in the field of gastric cancer over the past quarter century but also offers the reader a glimpse of the future by describing the ongoing surgical and oncological trials which focus on new treatment frontiers such as immunotherapy and target therapy. It also seeks to incorporate the latest discoveries based on molecular classifications. Further, the book reflects the findings and experiences of Italian experts belonging to the GIRCG (Italian Research Group for Gastric Cancer) and will offer an excellent guide for oncological surgeons in their daily practice of caring for patients affected by gastric cancer.
PART I. Epidemiology, Pathology and Diagnosis -- Chapter 1. Epidemiology and risk stratification as a guide for an effective screening strategy in the west -- Chapter 2. Carcinogenesis in the Era of Molecular Classifications -- Chapter 3. Carcinogenesis in the Era of Molecular Classifications -- Chapter 4. The new field of view of endoscopy and histological diagnosis -- Chapter 5. Hereditary gastric cancer -- Part II. Staging -- Chapter 6. EGDS and EUS -- Chapter 7. CT scan and PET/CT scan -- Chapter 8. CT scan and PET/CT scan -- Part III. Treatment -- Chapter 9. Early Gastric Cancer -- Chapter 10. Locally Advanced Gastric Cancer -- Chapter 11. The uncertainty of real life -- Chapter 12. Stage IV -- Chapter 13. Synopsis of Treatment Indications -- Part IV. New frontiers to improve prognosis -- Chapter 14. Tailored Treatment strategies based on new molecular classifications -- Chapter 15. Focus on Poorly Cohesive Gastric Cancer -- Chapter 16. Target Therapy and Immunotherapy -- Part V. Perioperative-management and Follow-up -- Chapter 17. The weight of nutrition in the therapeutic course -- Chapter 18. ERAS protocols -- Chapter 19. Complications after gastrectomy -- Chapter 20. Long-term outcome and follow-up -- Part VI. Technical notes in gastric surgery (Video Content) -- Chapter 21. Laparoscopic D2 dissection -- Chapter 22. D3 open dissection -- Chapter 23. Minimally invasive reconstruction in subtotal gastrectomy -- Chapter 24. Minimally invasive reconstruction total gastrectomy -- Chapter 25. PIPAC -- Chapter 26. Indocyanine green fluorescence -- Chapter 27. ESD.
Keywords: Surgery; Internal medicine; Gastrointestinal System; Molecular biology; Radiology; Surgery; Internal Medicine; Gastrointestinal System; Molecular Biology; Radiology; Stomach Neoplasms